(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2020)
Background/Objectives: Perinatal mortality rates are highest in Africa where it is more than five times higher than in developed regions. South Sudan has some of the worst health outcome indicators globally, in spite of modest improvements over the last five years. The aim of this study is to determine the magnitude and characteristic of women with early perinatal mortality at Juba Teaching Hospital, South Sudan. Methodology Study design: A cross-sectional study. Study site/setting: Juba Teaching Hospital maternal word. Study population: Comprised of mothers and their newborn babies delivered at JTH during the study period. Sampling: Consecutive sampling techniques was most appropriate for the selection of mothers who delivered their babies during the study period. Data collection & management: Data was analyzed using SPSS, version 23. Descriptive analysis was conducted to summarize characteristics of participants. Multivariable analysis conducted using binary logistic regression analysis to identify the predictors of EPNM. Statistical significance based on a p value of 0.05. Result: Early perinatal mortality rate was 122.3 per 1000 total birth with stillbirth rate of 82.7 per 1000 total births with majority attributable to fresh still births 14(41%). Factors associated with early perinatal mortality: Non-formal education ( OR=5; 95% CI 2.1-10.1 P val. <0.000) , pervious history of stillbirth, (OR = 2.6; 95% CI 1.1-6.3; p val. 0.04), ANC < 4 visit (OR=3.2, 95% CI 1.5-7.0; p val, 0.0005) and gestation age ≤ 36 weeks (OR= 5.1; 95% CI 2.4-11; p val. 0.0001), were associated with increased risk of EPNM. While parity of ≥ 4 (OR= 0.4; 95% CI 0.2-0.09; p val. 0.04), appeared to significantly, reduce EPNM among women delivered at JTH during the study period. Conclusions: The lack of formal education, younger maternal age, previous history of stillbirth, low antenatal clinic attendance and pre-term gestation increased the risk of early perinatal mortality among mothers delivered in JTH.